Anti-tumor necrosis factor ameliorates joint disease in murine collagen-induced arthritis. - Williams, R O (1992)
There is considerable evidence implicating tumor necrosis factor alpha (TNF-alpha) in the pathogenesis of rheumatoid arthritis. This evidence is based not only on the universal presence of TNF-alpha in arthritic joints accompanied by the upregulation of TNF-alpha receptors but also on the effects of neutralizing TNF-alpha in joint cell cultures. Thus, neutralization of TNF-alpha in vitro results in inhibition of the production of interleukin 1, which like TNF-alpha, is believed to contribute to joint inflammation and erosion. To determine the validity of this concept in vivo, the effect of administering TNF-neutralizing antibodies to mice with collagen-induced arthritis has been studied. This disease model was chosen because of its many immunological and pathological similarities to human rheumatoid arthritis. TN3-19.12, a hamster IgG1 monoclonal antibody to murine TNF-alpha/beta, was injected i.p. into mice either before the onset of arthritis or after the establishment of clinical disease. Anti-TNF administered prior to disease onset significantly reduced paw swelling and histological severity of arthritis without reducing the incidence of arthritis or the level of circulating anti-type II collagen IgG. More relevant to human disease was the capacity of the antibody to reduce the clinical score, paw swelling, and the histological severity of disease even when injected after the onset of clinical arthritis. These results have implications for possible modes of therapy of human arthritis.